2014 IEEE International Symposium on Circuits and Systems (ISCAS) 2014
DOI: 10.1109/iscas.2014.6865715
|View full text |Cite
|
Sign up to set email alerts
|

Improved margin multi-class classification using dendritic neurons with morphological learning

Abstract: We present an architecture of a spike based multiclass classifier using neurons with non-linear dendrites and sparse synaptic connectivity where each synapse takes a binary value. The learning in this model happens not through weight updates but through structural changes, i.e. a change of connectivity between inputs and dendrites. Hence, it is well suited for implementation in neuromorphic systems using address event representation (AER). We present a new learning rule that allows better generalization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…In [4], [6], the authors have suggested classifiers employing neurons with non-linear dendrites (NNLD) and binary synapses. Due to the presence of binary synapses, the learning in these type of architectures happen not by weight update but by morphological changes of the connections between inputs and dendrites.…”
Section: Background and Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…In [4], [6], the authors have suggested classifiers employing neurons with non-linear dendrites (NNLD) and binary synapses. Due to the presence of binary synapses, the learning in these type of architectures happen not by weight update but by morphological changes of the connections between inputs and dendrites.…”
Section: Background and Theorymentioning
confidence: 99%
“…Thus, these architectures are amenable for neuromorphic implementation employing AER protocols. We invite the reader to look into [4], [6] for a detailed description of the architectures and learning rules. In this paper, we present a circuit to implement the method proposed in [6] which has comparable performance as other spike based classifiers such as [7] but use 12X less synaptic resources.…”
Section: Background and Theorymentioning
confidence: 99%
See 3 more Smart Citations